THE EFFECT OF SERVICE QUALITY USING DIGITAL MACHINE ON CUSTOMER SATISFACTION (Case Study at PT. Bank Central Asia, Tbk Panakkukang Main Branch Office, Makassar) - Fince Fince (Scientium Management Review, 2022)
The rapid development of information technology and the internet has contributed to major changes in the banking service industry. Service quality is an important factor that supports customer satisfaction. This study aims to determine the effect of service quality on customer satisfaction. This research uses quantitative methods. The research population is the customers of the BCA Bank Panakkukang Main Branch Office, Makassar, totaling 200 customers with the sampling technique, saturated sampling so that the research sample is 200 customers. Data were collected using a questionnaire and analyzed using simple regression with the help of SPSS software, the variables in the study were service quality (X) and customer satisfaction (Y). The results of the study show that the service uses a digital machine at PT. Bank Central Asia Tbk. Panakkukang Makassar has an effect on customer satisfaction. This provides a good response to customer satisfaction in services using digital banking machines. With the dimensions of service quality consisting of Reliability, Tangibles, Responsiveness, and Assurance it is found that service quality using digital machines has a positive and significant effect on customer satisfaction.